KEPRIBADIAN TOKOH UTAMA AYRANIA DALAM NOVEL KIBLAT CINTA KARYA AWALIARRAHMAN PENDEKATAN PSIKOLOGI SASTRA - Anggita Putri; Devita Aprillia; Liska Indah Erlina; Siti Khairiah; Saptiana Sulastri (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the personality structure of the main character, Ayrania, in Awaliarrahman’s novel Kiblat Cinta through a literary psychology approach, specifically utilizing Sigmund Freud’s psychoanalytic theory. The method employed is descriptive-analytical qualitative research, with data collection involving a literature review through close reading and note-taking of the novel’s text corpus. The results of the analysis indicate that Ayrania’s personality is shaped by the complex dynamics between the id, ego, and superego. The id is characterized by impulsive, emotional drives and the desire for instant gratification. The ego operates based on the reality principle to temper the id’s impulses so they align with environmental conditions, as seen in polite behavior and anger management. Meanwhile, the superego acts as a moral compass dictating the character’s adherence to social norms, ethics, and responsibility.